Identifying the Application Areas and Utilization of Neural Networks in Quality Assessment: An exploration of the application areas and benefits of neural networks in quality assessment (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper explores the novel technique of neural networks and their application and their use in Quality Assessment. This is a study of neural network applications in reality situation. It gives a scientific classification of artificial neural networks (ANNs) and outfit the peruser with learning of flow and rising patterns in ANN applications research and region of center for analysts. As of now, artificial intelligence (machine learning, neural network, deep learning, automated), information security, huge information, distributed computing, web, and measurable science are for the most part hotspots and energizing subjects of information and communication technology (ICT). In late time's artificial neural networks (ANNs) has turned out to be famous and accommodating model for order, clustering, pattern recognition and prediction in numerous controls. ANNs are one kind of model for machine learning (ML) and has turned out to be generally focused to customary relapse and measurable models with respect to value. Ann's full applications can be assessed regarding information examination factors, for example, accuracy, processing speed, latency, performance, fault tolerance, volume, adaptability and union.